Migration timing and its determinants for nocturnal migratory birds during autumn migration. (30th April 2015) - La Sorte, Frank A.; Hochachka, Wesley M.; Farnsworth, Andrew; Sheldon, Daniel; Fink, Daniel; Geevarghese, Jeffrey; Winner, Kevin; Van Doren, Benjamin M.; Kelling, Steve; Chapman, Jason
<x xml:space="preserve">Abstract</x> This study provides the first comprehensive empirical evaluation of the timing and determinants of autumn migration for North American birds. The findings indicate migration timing is dictated by optimality strategies, modified based on the breadth and flexibility of migrant's foraging guild, with declining ecological productivity defining possible resource thresholds during which migration occurs with greatest intensity under weak high‐altitude winds. Breeding male blackpoll warbler, Setophaga striata. Photo credit: Brian L. Sullivan. <boxed-text content-type="graphic" id="jane12376-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>